Effect of Multidimensional Exercise Program for Improving Balance in Traumatic Brain Injury Patients (Medico Legal Update, 2020)
Background- Balance disorder is a common problem in post-TBI patients. In many research’s done beforetreatment is given mainly on motor component to improve balance in TBI patients. In this study we aregoing to give multidimensional protocol - sensory stimulations along with motor components. Balance is amain component of a patient for his mobility, many therapist concentrate on balance in chronic stage of TBIpatients, in this study we are going to give treatment in acute stage of TBI patients which will help themto recover fast. There is lack of research’s done on acute post TBI patients with multidimensional exerciseprogram for balance disorder. Indeed this made us to study the effect of multidimensional exercise programon balance disorder in TBI patients. Objectives- To find out the effectiveness of multidimensional exerciseprogram for improving balance control in mild TBI patients. To find out the effectiveness of multidimensionalexercise program for improving balance control in moderate TBI patients. To find out the effectiveness ofmultidimensional exercise program for improving balance control in severe TBI patient. METHOD- In thisstudy total 20 candidates were taken having impaired balance secondary to TBI from hospitals in karad.Their balance were assessed by berg balance scale and community balance and mobility scale. They weredivided into mild, moderate and severe TBI. A multidimensional exercise protocol of 6 week was givenfor improving balance and their balance was checked at 2nd, 4th, and 6th week by same BBS and CBMSscore. Later evaluation and interpretation of data was done. Result- The 20.8% improvement is seen inpre and post treatment BBS score and 8.82% improvement is seen in pre and post treatment CBMS scorein post TBI patients with balance impairment. Conclusion- On the basis of result it can be concluded thatmultidimensional exercise program is effective for improving balance in TBI patients.